The Status of Migratory Fish Passage and Barriers to Passage in the Connecticut River Watershed - U.S.Fish and Wildlife Service; (ScholarWorks@UMass Amherst, 1996)
This report provides information about barriers and fish passage in relation to the range of migratory fishes in the Connecticut River watershed. The data presented are available here for the first time in a single compilation. Maps are used to graphically display barrier and range data. These data were collected and processed by the United States Fish and Wildlife Service's Connecticut River Coordinator's Office with support from the Connecticut River Ecosystem Initiative of the National Biological Service (now the Biological Resources Division of the U.S. Geological Survey). Eleven State fisheries biologists responsible for anadromous fish management in the Connecticut River watershed (see Acknowledgements) were interviewed. Biologists reviewed maps (1:24,000 scale) of dams in the National Inventory of Dams (NID) Water Control Infrastructure Database (1993-1994, Federal Emergency Management Agency and Army Corps of Engineers) and undocumented barriers previously identified at 1:100,000 scale. The biologists provided locations and physical descriptions of barriers that are not included in the NID database, edited existing data on non-dam barriers, and corrected the locations of dams in the NID database. (The recently published 1995-1996 NID update was subsequently incorporated into the database.) Additionally, barriers within the historical range of anadromous fishes were qualitatively assessed for their obstructive impacts on the migration of the following species: Atlantic salmon, American shad, gizzard shad, blueback herring, alewife, sea lamprey, and American eel. The barrier locations and data were entered into a spatial database at 1:24,000 scale. It is important to emphasize that, in cases where quantitative data were unavailable, the data presented are based on the professional opinion of the biologists. Also, additional barriers likely exist that are not included herein due to lack of detailed field surveys. This is especially true for smaller streams. The passage status of some barriers for some species is unknown.